Impact of the Implementation of the National Rural Employment Guarantee Scheme in Some Selected Areas of Jharkhand - Mondal, Debabrata; Bandyopadhyay, A. K. (Prabandhan: Indian Journal of Management, 2013)
Generation of employment for the poor in the rural areas is one of the important components of the antipoverty and the rural development strategy adopted by the Ministry of Rural Development, Government of India. None of the earlier programmes could lead to the production of sustainable rural infrastructure. At the same time, none of those programmes ensured to the rural populace, the right to work, enshrined in the Constitution as a fundamental right to every citizen of our country. Keeping this shortcoming in mind, and to provide ensured wage employment to the rural population, the United Progressive Alliance (UPA) Government introduced the National Rural Employment Guarantee Act (NREGA) in February 2006. The present study was conducted to assess the impact of the National Rural Employment Guaranee Scheme in Bokaro district of Jharkhand in four villages; two from each of the Petarwar and Chas blocks. A total four villages namely Lukaia, Jaruatand, Radhanagar, and Pindrajora and 100 beneficiary households were selected for the present study. The data were collected during October-December, 2011. The data was analyzed using frequency, percentage, range and paired t-test. The study revealed that the beneficiary households have developed abundant self esteem and confidence through this job scheme. The biggest problem, according to the implementing agencies, is the lack of coordination among the various government departments and the refusal, especially by the railways and forest departments, to grant the no objection certificate.